(untitled) (European Journal of Emerging Technology and Discoveries, 2026)
Modified bitumen is a highly effective binding material with polymer or elastomeric additives, the strength, elasticity, and temperature stability of which are significantly enhanced. Its improved composition increases the crack resistance of the asphalt pavement, provides deformation resistance, and significantly extends its service life. Therefore, modified bitumen is used as the most reliable and long-term solution in heavy traffic, severe climate change, and high-load road structures.